2001
DOI: 10.1097/00075198-200108000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine

Abstract: Effective use of sedative-hypnotic and analgesic agents is an integral part of providing patient comfort and safety. Of the numerous drugs administered, benzodiazepines, propofol, and narcotics are the most popular. Even these proven, time-tested sedative-hypnotics and analgesics are not perfect, however, and modern intensive care demands a more ideal product. The development of dexmedetomidine, an alpha2-agonist, is an attempt to improve sedative/analgesic use and provide a drug that possesses the characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
176
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(186 citation statements)
references
References 37 publications
4
176
0
2
Order By: Relevance
“…Although the primary clinical use of dexmedetomidine is mainly for its effects on the central nervous system such as short-term sedation and antianxiety [9], more studies have shown that it can produce organ protective effects against ischemic and hypoxic injuries including cardioprotection, neuroprotection, and renoprotection [10e15]. In animal studies, dexmedetomidine has demonstrated anti-inflammatory effects by reducing the "cytokine storm" to reduce mortality and inhibit inflammatory responses in endotoxemic rats [16e18].…”
Section: Introductionmentioning
confidence: 99%
“…Although the primary clinical use of dexmedetomidine is mainly for its effects on the central nervous system such as short-term sedation and antianxiety [9], more studies have shown that it can produce organ protective effects against ischemic and hypoxic injuries including cardioprotection, neuroprotection, and renoprotection [10e15]. In animal studies, dexmedetomidine has demonstrated anti-inflammatory effects by reducing the "cytokine storm" to reduce mortality and inhibit inflammatory responses in endotoxemic rats [16e18].…”
Section: Introductionmentioning
confidence: 99%
“…The spinal antinociceptive actions of a 2 -adrenoceptors are mediated mainly by the a 2A -subtype (Jones et al, 1982;Khan et al, 1999;Kamibayashi & Maze, 2000;Malmberg et al, 2001), although a 2C -adrenoceptors also contribute (Fairbanks et al, 2002). Dexmedetomidine is a selective a 2 -adrenoceptor agonist currently approved for clinical use under intensive care conditions (Khan et al, 1999;Coursin & Maccioli, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…It has an a 2 /a 1 selectivity ratio of 1600 : 1, which is eight times more potent than clonidine (200 : 1). 5 DEX has been used effectively in intensive care to aid weaning from mechanical ventilation 6 and is being used increasingly in children. 7,8 However, the use of neuraxial DEX has not been reported before in children.…”
mentioning
confidence: 99%